Kebijakan Vaksinasi Covid-19 Berdasarkan Peraturan Presiden Nomor 14 Tahun 2021 Perubahan Atas Peraturan Presiden Nomor 99 Tahun 2020 Tentang Pelaksanaan dan Pengadaan Vaksinasi Dalam Upaya Penanggulangan Virus Covid-19 - Basar, Khoirul; Firdaus, Emilda; Junaidi, Junaidi (Jurnal Ilmiah Wahana Pendidikan, 2024)
In order to implement the maximum national vaccination program, President Joko Widodo issued Presidential Regulation (Perpres) Number 14 of 2021 concerning Amendments to Presidential Decree Number 99 of 2020 concerning Procurement of Vaccines and Implementation of Vaccinations in the Context of Overcoming the 2019 Corona Virus Disease (Covid-19) Pandemic. The Presidential Decree contains provisions governing the procurement of vaccines and the implementation of vaccinations in the context of dealing with the Covid-19 pandemic. Regarding administrative sanctions, it is one of the things regulated in this regulation. The administrative sanctions in question are aimed at people who have previously been declared as target recipients of the Covid-19 vaccine and basically this is contrary to Law No. 36 of 2019. People who then refuse to receive Covid-19 vaccination may be given administrative sanctions. These sanctions are stated in Article 13A paragraph (4) which states: "Every person who has been designated as a target recipient of the Covid-19 vaccine who does not take part in the Covid-19 vaccination as intended in paragraph (2) may be subject to administrative sanctions, in the form of, Postponement or termination of the provision of social security or social assistance. Postponement or termination of government administration services, and/or fines. This research method uses a normative juridical review method. This research is expected to increase knowledge for writers and readers regarding the Covid-19 Vaccination Policy Based on Presidential Regulation Number 14 of 2021 Amendments to Presidential Regulation Number 99 of 2020 concerning Implementation and Procurement of Vaccinations in Efforts to Control the Covid Virus -19.The legal policy that the public will accept if they refuse to be given the Covid-19 vaccine, in Article 13A paragraph 4 and paragraph 2, is that every person who has been designated as a target recipient of the Covid-19 vaccine who does not take part in the Covid-19 vaccination, may be subject to administrative sanctions in the form of: postponement or termination of the provision of social security or social assistance; Delays in administrative services cause obstacles to the implementation of controlling the spread of Covid-19. In addition to being subject to sanctions, sanctions can be imposed in accordance with the provisions of Law Number 4 of 1984 concerning infectious disease outbreaks. The appropriate government policy regarding the issue of implementing vaccination in efforts to contain the Covid-19 virus is to review Presidential Decree No. 14 Article 13 A regarding the obligation that every citizen is obliged to carry out vaccination and if this is not carried out, administrative sanctions will be imposed; re-collect data regarding vaccination recipients, especially the elderly and people who have congenital diseases; and aligning the presidential decree with the contents of Health Law Number 36 of 2009 that every citizen has the right to determine the health facilities they will receive without any coercion from any party.